2019
DOI: 10.1177/0042098018813041
|View full text |Cite
|
Sign up to set email alerts
|

Smart urbanism? ICTs for water and electricity supply in Nairobi

Abstract: In recent years, the study of urban infrastructure has become central to examining African cities. This paper is a contribution to this scholarship. Of particular interest is the interface between telecommunications and urban water and electricity utility systems. I examine the degree to which ICT deployments for urban water and electricity supply shape and are shaped by the urban context of Nairobi, Kenya. I show how in recognition of the city’s splintering and fragmentation, service providers have employed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…The micro‐payments feasible via mobile contracts enable increasing market‐based consumption of digital products such as games, ringtones and mobile services (Aker & Mbiti, ). They also allow new competitive markets to be created for low‐income groups, for services such as water and energy (Guma, ). Induction of informal retailers as mobile handset or mobile money retailers incorporates them into more formal chains of market relations (Foster & Heeks, ; Kim et al, ). Curve : alongside Shift , this is a core construct of those writing about digital and development. Under various terminologies—“digital capitalism” (Schiller, ), “informational capitalism” (Castells, ), “distributed capitalism” (Zuboff, ) and “platform capitalism” (Srnicek, )—the main argument is that, for the dominant mode of economic organisation, the “ substance is continuous from previous forms of capitalism, whereas the level of form , from industrial to informational, and praxis , from hierarchical to decentralized operations and management, is characterized by change” (Gripenberg, :120). …”
Section: Digital Economymentioning
confidence: 99%
“…The micro‐payments feasible via mobile contracts enable increasing market‐based consumption of digital products such as games, ringtones and mobile services (Aker & Mbiti, ). They also allow new competitive markets to be created for low‐income groups, for services such as water and energy (Guma, ). Induction of informal retailers as mobile handset or mobile money retailers incorporates them into more formal chains of market relations (Foster & Heeks, ; Kim et al, ). Curve : alongside Shift , this is a core construct of those writing about digital and development. Under various terminologies—“digital capitalism” (Schiller, ), “informational capitalism” (Castells, ), “distributed capitalism” (Zuboff, ) and “platform capitalism” (Srnicek, )—the main argument is that, for the dominant mode of economic organisation, the “ substance is continuous from previous forms of capitalism, whereas the level of form , from industrial to informational, and praxis , from hierarchical to decentralized operations and management, is characterized by change” (Gripenberg, :120). …”
Section: Digital Economymentioning
confidence: 99%
“…A subsequent study by [74] and later by [75] found that Nairobi city has a huge unequal and inequitable consumption of the available conventional water hence forcing residents to rely on water vending. Further, a most recent revelation by [76] showed that only 50% of Nairobi residents receive clean piped water. He added further, that out of this, a mere 40% has a 24-hour access.…”
Section: Water Supply Reliabilitymentioning
confidence: 99%
“…In recent years Nairobi has become a key node within global ICT networks and, as evidenced by the Nairobi Integrated Urban Development Master Plan (NIUPLAN) and the Nairobi Metro 2030 Vision, ICT and smart technologies are key both in improving the infrastructure of the city and pushing the country toward a knowledge based economy (Hanna, 2016;Guma, 2019). With the landing of fiber optic cabling (Waema and Ndung'u, 2012), the establishment of supportive open data initiatives (Ndemo, 2015), the development of the mobile banking phenomenon M-Pesa (Jack and Suri, 2011) and an emergence of innovation hubs across the country (Mwaniki, 2017), Nairobi has become a hotspot of digital innovation and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…With the landing of fiber optic cabling (Waema and Ndung'u, 2012), the establishment of supportive open data initiatives (Ndemo, 2015), the development of the mobile banking phenomenon M-Pesa (Jack and Suri, 2011) and an emergence of innovation hubs across the country (Mwaniki, 2017), Nairobi has become a hotspot of digital innovation and implementation. Although academic and media attention often focuses on ICT's infrastructural implementation within wealthier areas of the city (Guma, 2019), advanced digital technologies such as those of the Internet of Things (IoT) are increasingly becoming embedded within informal urban settlements such as Mathare, Mukuru Kwa Njenga, and Kibera and the infrastructures that serve them (Guma, 2019;Chambers and Evans, forthcoming). As a consequence of ICTs integration within the infrastructures of Nairobi's informal urban settlements and against a backdrop of rapid uptake of mobile payment services such as m-pesa, digital platforms have begun to emerge as new points of engagement between citizens and infrastructures in the city.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation